Effective academic writing 1 : the paragraph - Savage, Alice; Shafiei, Masoud (New York, USA : Oxford University Press, 2007)
Presents models of student essays which aim to enhance learners' comprehension of writing modes. This work covers units that include writing tasks and specific rhetorical focus and language focus points. Each unit features self-contained lessons
EDU
Keywords: English language -- Rhetoric -- Problems, exercises, etc; English language -- Paragraphs -- Problems, exercises, etc; English language -- Textbooks for foreign speakers; Academic writing -- Problems, exercises, etc